Cytisine versus varenicline for smoking cessation for Māori (the indigenous people of New Zealand) and their extended family: protocol for a randomized non‐inferiority trial. (9th November 2018) - Walker, Natalie; Smith, Barry; Barnes, Joanne; Verbiest, Marjolein; Kurdziel, Tomasz; Parag, Varsha; Pokhrel, Subhash; Bullen, Chris
Abstract: Background and aims: Cytisine, a nicotinic acetylcholine receptor partial agonist (like varenicline) found in some plants, is a low‐cost, effective smoking cessation medication that may appeal to Māori [the indigenous people of New Zealand (NZ)]. The RAUORA trial aims to determine the effectiveness, safety and cost‐effectiveness of cytisine (Tabex ® ) versus varenicline (Champix ® ) for smoking cessation in Māori and the whānau (extended family) of Māori. Design: Pragmatic, community‐based, open‐label randomized non‐inferiority trial. Setting: Lakes District Health Board region, NZ. Participants: Daily smokers ( n  = 2140) who self‐identify as Māori or whānau of Māori, and are: aged ≥ 18 years, motivated to quit smoking in the next 2 weeks, eligible for subsidized varenicline, able to provide verbal consent and have daily access to a mobile phone/internet. Recruitment uses multi‐media advertising. Intervention and comparator: Participants are randomized (1 : 1 ratio) to receive a prescription for 12 weeks of cytisine tablets [following the manufacturer's dosing regimen for 25 days, then one 1.5‐mg tablet every 6 hours (two per day) until 12 weeks] or varenicline tablets (following the manufacturer's dosing regimen). Both groups receive brief stop‐smoking advice from the prescribing doctor and withdrawal‐orientated behavioural support via community‐based stop‐smoking counselling services (frequency, duration and mode of delivery tailored for participants) or a research assistant (six weekly 10–15‐minute calls). Participants are advised to reduce their smoking over the first 4 days of treatment, with day 5 as their designated quit‐date. Measurements: The primary outcome is carbon monoxide‐verified continuous abstinence at 6 months post‐quit date. Secondary outcomes at 1, 3, 6 and 12 months post‐quit date include: self‐reported continuous abstinence, 7‐day point prevalence abstinence, cigarettes per day, time to (re)lapse, adverse events, treatment adherence/compliance, treatment acceptability, nicotine withdrawal/urge to smoke and health‐care utilization/health‐related quality of life. Comments: This trial compares cytisine and varenicline when used by the indigenous people of NZ and their extended family for smoking cessation.